Knowledge, attitude, and practice of patients with oral diseases toward oral examinations: a cross-sectional survey study - Wang, Wei (Frontiers in Public Health, 2024)
Background: Properly adhering to oral hygiene and medical care is an important public health issue. Several studies examined the knowledge, attitudes, and practices (KAP) toward oral care in various populations and generally reported relatively sufficient knowledge but unfavorable attitudes and poor practice. However, no previous studies have examined the KAP toward oral examinations among Chinese patients with oral diseases. This study aimed to examine the KAP toward oral examinations among patients with oral diseases in China. Methods: This cross-sectional study was conducted in patients with oral diseases who visited The Affiliated Stomatological Hospital of Tongji University between December 2023 and February 2024. Data collection and KAP scores assessment were performed using a self-designed questionnaire. Results: A total of 519 valid questionnaires were included, with 292 females. The mean knowledge, attitude, and practice scores were 6.42±2.47 (possible range: 0-9 points), 35.04±5.68 (possible range: 10-50 points), and 16.22±2.05 (possible range: 4-20 points), respectively, indicating sufficient knowledge, positive attitudes, and proactive practice. Pearson’s correlation analysis showed that knowledge was positively correlated to attitude (r=0.468, P<0.001) and practice (OR=0.416, P<0.001). Attitude was positively correlated to the practice (r=0.503, P<0.001). Moreover, the structural equation model showed that knowledge influenced attitude (estimate=1.010, P<0.001) and practice (estimate=0.169, P<0.001). Attitude influenced practice (estimate=0.122, P<0.001). The frequency of oral examination per year influenced knowledge (estimate=-0.761, P<0.001) and practice (estimate=-0.515, P<0.001). Expenses for oral disease per year influenced attitude (estimate=0.537, P<0.001). Conclusion: Patients with oral disease might have sufficient knowledge, positive attitude, and proactive practice toward oral examinations. Specific knowledge items were identified to require improvements.